PENGGUNAAN KALIANDRA (Calliandra calothyrsus), Indigofera sp. DAN CAMPURANNYA DALAM RANSUM SEBAGAI PENGGANTI KONSENTRAT TERHADAP PRODUKTIVITAS DOMBA GARUT JANTAN - Nurjannah, Syifa; Ayuningsih, Budi; Hernaman, Iman; Susilawati, Iin (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2019)
This research aimed to determine the productivity of livestock. Feed availability in the dry season is one of the causes low productivity of livestock. Calliandra calothyrsus (C. calothyrsus) and Indigofera sp. are leguminosae plant that resistant to drought and could produce high productivity. Both can be used as a sustainable animal feed and reduce production costs. The animal used was weaned male sheep. The method used was Completely Randomized Design (CRD), with six treatments (P0 : 70% Grass + 30% Concentrate, P1 : 70% P. Grass + 15% Concentrate + 15% C. calothyrsus, P2 : 70% Grass + 15% Concentrate + 15% Indigofera sp., P3 : 70% Grass + 30% C. calothyrsus, P4 : 70% Grass + 30% Indigofera sp., P5 : 70% Grass + 15% C. calothyrsus + 15% Indigofera sp.) and four replication. The observed variables were dry matter consumption, average daily gain (ADG), and feed conversion. The results showed that the used of 15% C. calothyrsus and 15% Indigofera sp. was more efficient. The highest value of dry matter consumption (P<0,05) and average daily gain (P>0,05) obtained P5 treatment, respectively 508,80 g/day and 45,36 g/day, while the lowest value of feed conversion (P>0,05) obtained P0 (11,69) which was not significantly different with P5 (11,75).Â Keywords: Calliandra calothyrsus, Indigofera sp., weaned male sheep, the productivity of livestock